Citral inibe proliferação de Candida albicans isoladas de usuários de próteses dentais removíveis - Freire, Julliana Cariry Palhano (2017)
Removable prostheses are considered to be potentially facilitators of prosthetic stomatitis. Candida sp. infection is a very common cause, with Candida albicans being the most prevalent and most frequently associated with this pathology. The study of natural herbal products to combat this type of infection appears as an alternative method of treatment, since the resistance of the species to the licensed antifungal agents as well as the adverse effects and toxicity of these drugs has increased. This research analyzed the antifungal activity of citral, selected from a screening, against clinical strains of C. albicans isolated from prosthesis users. Twenty-one isolates were identified and identified as one standard (ATCC 76645). Initially, a screening was performed for the selection of a natural product, with the following essential oils: Mentha piperita L. (Briq); Origanum Vulgare; Zingibre officinale L. and citral and limonene phytochemicals. Among them, citral produced better antifungal response and was selected for biological assays. The test products were composed by the citrus phytoconstituent and nystatin. The minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) were determined by the microdilution method. Micromorphological analysis, microbial death kinetics and modulation were performed. Data were analyzed descriptively. The CIM and MFC of citral were established at the concentration of 32 μg/mL, showing fungicidal activity. All yeasts of clinical origin were found to be resistant to nystatin, but C. albicans ATCC 76645 was sensitive, with MIC corresponding to 256 μg/mL. There was a change in the micromorphology of the strains exposed to the citral, verifying less fungal structures. In the kinetics of microbial death, the clinical strain showed a reduction in growth equal to 3 log10 CFU/mL in two hours of citral exposure in the MIC and CIMx2. There was no fungal growth in the evaluated times of the standard strain when exposed to citral concentrations, as well as clinical C. albicans submitted to CIMx4. Citral did not modulate the activity of nystatin on the resistance of the studied strains. This research revealed the promising potential of citral, being characterized as a fungicidal agent, and the highlight of the resistance of clinical strains of C.albicans to nystatin.